Herd Behaviour and COVID-19 Intervention - Sharma, Sushil Prasad; Aryal, Bibek; Thagunna, Karan Singh (Journal of Business and Social Sciences Research, 2024)
The paper attempted to confirm the rational assets pricing model by examining the herd behaviour in extreme market returns and examining the COVID-19 intervention by comparing before COVID-19, during COVID-19 and after COVID-19 period. Cross Sectional Standard Deviation (CSSD) calculated as the index and further regressed by using dummy variables (Extreme upper tail market returns =1, otherwise = 0). For the better inferences stationarity of time series data were checked by both graphically and Augmented Dickey –Fuller test in all three states of COVID-19. Finally, the Cumulative-Sum (CUSUM) test was conducted to check the parameter stability of the regression model. The finding of the study supports the rational asset pricing models, meaning that there is no presence of herding in NEPSE in extreme upper tail returns. But it rejects the rational asset pricing models in case of extreme lower market returns and in COVID-19 period. For better affirmation of rational assets pricing models, future research can extend the work by addressing the market characteristics, such as: trading volume, volatility, and liquidity.